Exposed to the Media: Intentions to Gamble and Problem Gambling - Renata Korsakiene; Neringa Vilkaite-Vaitone; Laima Jeseviciute-Ufartiene (SAGE Open)
The study combines the social cognitive theory and the theory of planned behavior to predict the effects of media exposure and behavior of customers on intentions to gamble and problem gambling. Based on the 1,777 observations of Lithuanian gamblers, a robust path analysis procedure revealed that media exposure can strengthen attitudes, subjective norms, and perceived control. In turn, attitude and perceived control can increase the intention to gamble. However, subjective norms were found to have a negative impact on gambling intention. The study also found that gambling intention directly affects problem gambling severity. By combining social cognitive theory and theory of planned behavior, the study provides a clearer understanding of how gambling exposure in various forms of media can affect attitudes, subjective norms, and perceived behavioral control. These findings enhance the discussion on gambling behavior and have important implications for policymakers, health organizations, and marketers.